2018
DOI: 10.1080/1612197x.2018.1444077
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the association of self-regulated learning skills and physical activity in Hong Kong Chinese and Scottish adolescents

Abstract: This study examines the role of self-regulated learning (SRL) skills in physical activity (PA) among Hong Kong Chinese (HK) and Scottish adolescents. Methods Using a cross-sectional design, 480 HK (aged 11-19; mean age = 14.93 years, SD = 1.77, male = 61.3%) and 411 Scottish, aged 12-16 years (mean = 13.84; male = 47.9%) healthy adolescents participated in this study. PA was measured with the Godin Leisure-Time Questionnaire (Godin & Shephard, 1985). SRL was measured for Chinese (SRL-SRS-C; Pitkethly & Lau, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 73 publications
0
3
0
6
Order By: Relevance
“…Another limitation of this study is the lack of consideration of other psychological correlates of PA such as intrinsic/autonomous motivation Edward L. Deci & Ryan, 1985), self-regulation (Pitkethly, Lau, & Maddison, 2018), and self-perception (Sales, Levinger, & Polman, 2017). Indeed, research has demonstrated that a range of psychological factors can contribute to PA behavior (Biddle et al, 2011;.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 98%
“…Another limitation of this study is the lack of consideration of other psychological correlates of PA such as intrinsic/autonomous motivation Edward L. Deci & Ryan, 1985), self-regulation (Pitkethly, Lau, & Maddison, 2018), and self-perception (Sales, Levinger, & Polman, 2017). Indeed, research has demonstrated that a range of psychological factors can contribute to PA behavior (Biddle et al, 2011;.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 98%
“…Furthermore, self-reflection has been associated with better cardiovascular health, 21 recovery from psychological ill-health, 22,23 and healthier lifestyles. 48 Stress responses, health, and lifestyle factors are associated with AD risk 2 ; thus, self-reflection may affect AD-sensitive markers via one of these pathways. To this end, we investigated the association between self-reflection and health and lifestyle behaviors that have been associated with cognitive functioning and AD risk (i.e., LIBRA) and in exploratory analyses assessed whether self-reflection affects AD-sensitive markers independently of these behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…La educación superior reúne el mayor número de investigaciones que contienen las variables de autorregulación del aprendizaje, metacognición, aprendizaje autónomo o capacidad autorreguladora (Arenas, 2017;Díaz et al, 2017;Fosado et al, 2018;Sanabria et al, 2017;Freiberg et al, 2017;García et al, 2017;Melgar y Elizondo, 2017;Miño-Puigcercós et al, 2019;Kelly, 2017;Sun et al, 2018). En el nivel medio superior se identifican dos investigaciones desarrolladas en México (Berridi y Martínez, 2017;Rodríguez y González, 2018), mientras que, en el nivel de secundaria o equivalente, se identificaron ocho investigaciones de España, Colombia, Argentina, Holanda, China y Escocia (Alvarez et al, 2018;Badia y Daura, 2018;Gasco-Txabarri, 2017;Muchiut et al, 2018;Muñoz-Muñoz y Ocaña, 2017;Olivo, 2017;Pitkethly, Lau y Maddison, 2018;Raaijmakers, et al, 2018). En el nivel de educación primaria o equivalente, el número de investigaciones se reduce un poco más (Tabla 2).…”
Section: Discussionunclassified